Bantuan Hukum Terhadap Anak Korban Tindak Pidana Kekerasan Seksual Di Indonesia - Adinda Khairun Nisa; Nicka Tri Mulyasari (Jurnal Risalah Hukum, 2023)
Sexual violence against children and women is a problem that is rife lately. The number of children who become victims of sexual violence cases is due to the mindset that these children are considered helpless. The government and also related institutions to prevent cases of sexual violence against children and women have made various efforts, for example, in terms of policies and also firm regulations.  This research uses descriptive research with the type of research is normative juridical. In providing protection for child victims of sexual violence and providing legal assistance for child victims of sexual violence, many obstacles are still encountered. These constraints are both constraints from internal factors and also constraints from external factors. The implementation of legal protection for child victims of sexual violence, in reality, still cannot be implemented optimally following the policies of existing laws and regulations in Indonesia. Enforcing the law in the criminal act of sexual violence against children, it can fulfill a sense of justice for the victim, the victim's family, and the community by imposing maximum punishment and strict sanctions for perpetrators of sexual violence against children.